Anticholinergics combined with alpha‐blockers for treating lower urinary tract symptoms related to benign prostatic obstruction - Pang, Ran (Cochrane Database Syst Rev, 2021)
BACKGROUND: Lower urinary tract symptoms (LUTS) due to benign prostatic obstruction (BPO) represent one of the most common clinical complaints in men. Alpha‐blockers are widely used as first‐line therapy for men with LUTS secondary to BPO, but up to one third of men report no improvement in their LUTS after taking alpha‐blockers. Anticholinergics used in addition to alpha‐blockers may help improve symptoms but it is uncertain how effective they are.  OBJECTIVES: To assess the effects of combination therapy with anticholinergics and alpha‐blockers in men with LUTS related to BPO. SEARCH METHODS: We performed a comprehensive search of medical literature, including the Cochrane Library, MEDLINE, Embase, and trials registries, with no restrictions on the language of publication or publication status. The date of the latest search was 7 August 2020. SELECTION CRITERIA: We included randomized controlled trials. Inclusion criteria were men with LUTS secondary to BPO, ages 40 years or older, and a total International Prostate Symptom Score of 8 or greater. We excluded trials of men with a known neurogenic bladder due to spinal cord injury, multiple sclerosis, or central nervous system disease, and those examining medical therapy for men who were treated with surgery for BPO. We performed three comparisons: combination therapy versus placebo, combination therapy versus alpha‐blockers monotherapy, and combination therapy versus anticholinergics monotherapy. DATA COLLECTION AND ANALYSIS: Two review authors independently screened the literature, extracted data, and assessed risk of bias. We performed statistical analyses using a random‐effects model and interpreted data according to the Cochrane Handbook for Systematic Reviews of Interventions. We used the GRADE approach to rate the certainty of evidence. MAIN RESULTS: We included 23 studies with 6285 randomized men across three comparisons. The mean age of participants ranged from 54.4 years to 73.9 years (overall mean age 65.7 years). Of the included studies, 12 were conducted with a single‐center setting, while 11 used a multi‐center setting. We only found short‐term effect (12 weeks to 12 months) of combination therapy based on available evidence. Combination therapy versus placebo: based on five studies with 2369 randomized participants, combination therapy may result in little or no difference in urologic symptom scores (mean difference (MD) –2.73, 95% confidence interval (CI) –5.55 to 0.08; low‐certainty evidence). We are very uncertain about the effect of combination therapy on quality of life (QoL) (MD –0.97, 95% CI –2.11 to 0.16; very low‐certainty evidence). Combination therapy likely increases adverse events (risk ratio (RR) 1.24, 95% CI 1.04 to 1.47; moderate‐certainty evidence); based on 252 adverse events per 1000 participants in the placebo group, this corresponds to 61 more adverse events (95% CI 10 more  to 119 more) per 1000 participants treated with combination therapy. Combination therapy versus alpha‐blockers alone: based on 22 studies with 4904 randomized participants, we are very uncertain about the effect of combination therapy on urologic symptom scores (MD –2.04, 95% CI –3.56 to –0.52; very low‐certainty evidence) and QoL (MD –0.71, 95% CI –1.03 to –0.38; very low‐certainty evidence). Combination therapy may result in little or no difference in adverse events rate (RR 1.10, 95% CI 0.90 to 1.34; low‐certainty evidence); based on 228 adverse events per 1000 participants in the alpha‐blocker group, this corresponds to 23 more adverse events (95% CI 23 fewer to 78 more) per 1000 participants treated with combination therapy. Combination therapy compared to anticholinergics alone: based on three studies with 1218 randomized participants, we are very uncertain about the effect of combination therapy on urologic symptom scores (MD –3.71, 95% CI –9.41 to 1.98; very low‐certainty evidence). Combination therapy may result in an improvement in QoL (MD –1.49, 95% CI –1.88 to –1.11; low‐certainty evidence). Combination therapy likely results in little to no difference in adverse events (RR 1.26, 95% CI 0.81 to 1.95; moderate‐certainty evidence); based on 115 adverse events per 1000 participants in the anticholinergic alone group, this corresponds to 4 fewer adverse events (95% CI 7 fewer to 13 more) per 1000 participants treated with combination therapy. AUTHORS' CONCLUSIONS: Based on the findings of the review, combination therapy with anticholinergics and alpha‐blockers are associated with little or uncertain effects on urologic symptom scores compared to placebo, alpha‐blockers, or anticholinergics monotherapy. However, combination therapy may result in an improvement in quality of life compared to anticholinergics monotherapy, but an uncertain effect compared to placebo, or alpha‐blockers. Combination therapy likely increases adverse events compared to placebo, but not compared to alpha‐blockers or anticholinergics monotherapy. The findings of this review were limited by study limitations, inconsistency, and imprecision. We were unable to conduct any of the predefined subgroup analyses.